Relationship between fortilin levels and coronary ischemia in heart failure - Gökçek, Sümeyra; Aydın, Cihan; Demirkıran, Aykut; Alpsoy, Şeref (The European Research Journal, 2024)
Objective: Fortilin is a multifunctional protein that protects cells against apoptosis. We aimed to investigate the levels of fortilin in patients with heart failure. Methods: Patients with ejection fraction (EF) below 40% were divided into two groups according to coronary angiography results: those with ischemic heart failure (Group 1) and those with non-ischemic heart failure (Group 2). Patients with normal anatomy and EF over 50% were included in the control group (Group 3). Results: A total of 119 patients were prospectively included in the study. A total of 81 patients (41 patients with ischemic heart failure and 40 patients with non-ischemic heart failure) were included in the heart failure group. 38 patients with EF >50 and normal coronary anatomy were included in the control group. There was no significant difference in serum fortilin levels between the study groups (Group 1: 5.5±2.6 ng/mL, Group 2: 6.1±3.8 ng/mL, and Group 3: 5.6±3.6 ng/mL; P=0.693). Fortilin did not show a correlation with any other variables. Conclusion: In our study, there was no significant difference in fortilin levels between the groups, and no relationship was found between coronary ischemia and fortilin levels in heart failure.